ARANSEMEN DENDANG TALAGO BIRU - Dhaniel Rahmat Ameva; Ardipal Ardipal; Wimbrayardi Wimbrayardi (SENDRATASIK UNP, 2013)
Abstract The music arrangement of Talago Biru was inspired by (1) the melody of accompaniment music in dance performance and as an instructional material in the Dendang course. The purpose of this artwork is (2) to clarify that the musical arrangement is a new model of music arrangement based the writer’s ability and to add more value of an artwork without eliminating the main idea or the core of Talago Biru Music arrangement. The form presented in this artwork is (3) the combination of traditional music (dendang) with western musical styles that have been tied to the bars pattern without eliminating the typical character of dendang   Kata kunci : Model garapan baru, Musik Tradisonal, Musik Modern.